Bilateral Wilms Tumor: A Surgical Perspective - Andrew J. Murphy; Andrew M. Davidoff (MDPI AG, 2018)
Historically, the management of bilateral Wilms tumor (BWT) was non-standardized and suffered from instances of prolonged chemotherapy and inconsistent surgical management which resulted in suboptimal renal and oncologic outcomes. Because of the risk of end-stage renal disease associated with the management of BWT, neoadjuvant chemotherapy and nephron-sparing surgery have been adopted as the guiding management principles. This management strategy balances acceptable oncologic outcomes against the risk of end-stage renal disease. A recent multi-institutional Children’s Oncology Group study (AREN0534) has confirmed the benefits of standardized 3-drug neoadjuvant chemotherapy and the utilization of nephron-sparing surgery in BWT patients; however, less than 50% of patients underwent bilateral nephron-sparing surgery. The coordination of neoadjuvant chemotherapy and the timing and implementation of bilateral nephron-sparing surgery are features of BWT management that require collaboration between oncologists and surgeons. This review discusses the surgical management strategy in the context of BWT disease biology, with an emphasis on timepoints during therapy at which surgical decision making can greatly impact this disease and minimize long-term toxicities.